MODEL OF EXPERIMENTAL PRAGMATISM IN ARCHITECTURE - Widiastuti, Kurnia; Ikaputra, Ikaputra (Border: Jurnal Arsitektur, 2020)
The discourse on experimental pragmatism, as a paradigm in architecture is very limited. Different than experimental architecture, pragmatism in experimental pragmatism architecture adds a dimension of rational actualization in a design speculation, so that it has the potential to answer the challenges of changing world. This study aims to obtain experimental pragmatism paradigm model in architecture using content analysis method. It was learned that experimental pragmatism (PE)in architecture can be modelled as design paradigm that prioritizes the strength of discovery goals (T) and their actualization in the experiment process (P) and design output (L) according to their attributes. Attributes of ‘process’ are method and parameter (MP) while atributs of ‘outputs’ are characteristic and parameters (SP). Experimental architecture and experimental pragmatism are equally related to aspects of goals, processes and outcomes, but differ in emphasis. Experimental architecture emphasizes aspects of the process, while architectural pragmatism emphasizes aspects of goals that are more related to the non-physical stages of architectural programming.